2021
DOI: 10.1080/00913367.2020.1870586
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ad Sequence and Privacy Concerns in Personalized Advertising: An Eye-Tracking Study into Synced Advertising Effects

Abstract: Synced advertising is a relatively new strategy in which ads are personalized based on concurrent media usage. The aim of this study was to explore whether the sequence in which TV commercials and tablet ads were shown in synced advertising affected consumers' memory and attention toward advertisements in both media. Because of public debate about privacy concerns related to personalized advertising, we examined the moderating role of consumers' privacy concerns as a personal factor. An eye-tracking experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Personalized advertising has received a high degree of attention in recent years, and synchronous and online advertising has become the focus of research, which has greatly changed consumer engagement [7]. Studies have shown that consumer purchase intentions are directly related to advertising strategies, some of which are more vivid, often using reasonable contrast colors, and also emphasize the importance of dynamic animation to change consumer attitudes [8].…”
Section: Overview Of Previous Relevant Studiesmentioning
confidence: 99%
“…Personalized advertising has received a high degree of attention in recent years, and synchronous and online advertising has become the focus of research, which has greatly changed consumer engagement [7]. Studies have shown that consumer purchase intentions are directly related to advertising strategies, some of which are more vivid, often using reasonable contrast colors, and also emphasize the importance of dynamic animation to change consumer attitudes [8].…”
Section: Overview Of Previous Relevant Studiesmentioning
confidence: 99%
“…1. Although numerous studies have examined speech acts in a variety of linguistic contexts, little attention has been paid to their use in advertising (Al-Najjar & Bishara, 2018;Naufalina, 2017;Sukarini, 2022). Furthermore, there is a dearth of research within the field of advertising that focuses specifically on the persuasive strategies employed through speech acts.…”
Section: Related Studiesmentioning
confidence: 99%
“…However, Bluetooth linkage to external device and GPS running in the background make the users passive and their control is minimized. Furthermore, although users may encounter privacy concerns (Jung et al, 2015;Ham, 2016;Segijn et al, 2021), most are not willing to fulfil the requirements of this concern 1 . This indifference, which is called the privacy paradox (Barnes, 2006;Kokolakis, 2017) has proven to be extremely common among mobile phone users (Zhou, et al, 2011;Shklovski et al, 2014;Taddicken, 2014;Gerber et al, 2018;Han et al, 2019;Sanchez et al, 2019;Afolabi et al, 2020).…”
Section: Theory Reviewmentioning
confidence: 99%